Fatal methadone and heroin overdoses: time trends in England and Wales. Issue 4 (August 1997) - Neeleman, J; Farrell, M
Abstract : STUDY OBJECTIVE: Although the total number of self poisonings in England and Wales has dropped by 32%, the number involving methadone and/or heroin rose by 900% in 1974-92. Because of concern about the role of methadone in this increase, the part played by methadone and heroin in poisoning deaths in England and Wales in 1974-92 was investigated. DESIGN: A proportional mortality design was used to study whether the ratio between deaths involving methadone or heroin and other substances had increased. The time trend was examined with logistic regression. SETTING: England and Wales, 1974-92. SUBJECTS: Accidental, undetermined, and suicidal poisoning deaths (n = 43, 231). MAIN RESULTS: The proportions of poisoning deaths involving methadone (alone or in combination with heroin) rose by 80% (95% CI 69%, 92%) per 3 year period. The proportion of poisoning deaths involving heroin without methadone rose by 76% (95% CI 60%, 93%) per 3 year period. Similar results were obtained when poisoning deaths were examined in relation to gender and legal category (suicide and undetermined versus accidental deaths). CONCLUSIONS: The impact of opiate addiction on rates of death by poisoning is rising quickly. This may reflect the growth of the addict population and is an important public health problem. There is no evidence that methadone's involvement in these deaths has risen disproportionately in relation to that of heroin up to 1992.